Cytotoxic sesquiterpene lactones and lignans from Cousinia turkmenorum Bornm (Asteraceae). Issue 23 (1st December 2022) - Norouzi, Saeed; Iranshahy, Milad; Iranshahi, Mehrdad; Shakeri, Abolfazl
Abstract: Seven sesquiterpene lactones, chlorophyssopifolin E (1 ), aguerin B (2 ), repdiolide triol (3 ), solistitiolide (4 ), aitchisonolide (5 ), sinicin B (6 ), cynaropicrin (7 ), along with four lignans arctigenin (8 ), arctiin (9 ), matairesinol (10 ), and matairesinoside (11 ) were isolated for the first time from the aerial parts of Cousinia turkmenorum Bornm. Among the isolated compounds, aguerin B (2 ) showed the most cytotoxic activity against MCF7 cell lines with IC50 value of 18.9 μM. Findings of this study could be useful for the development of new anticancer agents from nature. Graphical Abstract: UF0001